Social Construction of Da’wah by the Executive Board of Nahdlatul Ulama in Indonesia - Ladin Ladin; Akhyak Akhyak; Abd. Aziz (International Journal of Social Science and Humanity, 2025)
The Da’wah Institution of Nahdlatul Ulama (NU), as part of Indonesia's largest Islamic organization, faces challenges in adapting to social dynamics, the digital revolution, and the rise of radicalism. In an increasingly diverse and fast-changing society, NU must develop da’wah strategies that are not only moderate and contextual but also adaptable to contemporary shifts. This study aims to explore how NU's social construction of da’wah is structured epistemologically, ontologically, and strategically to strengthen Islam’s role as rahmatan lil 'alamin, promoting social harmony and national unity. The research adopts a multisite case study approach at the Da’wah Institution of the NU Executive Board, employing qualitative methods through document analysis and in-depth interviews. The findings indicate that NU’s da’wah social construction integrates three main dimensions. Epistemologically, NU’s da’wah is grounded in authentic and contextual knowledge, allowing the dissemination of Islamic values in a peaceful, moderate, and inclusive way. Ontologically, the Da’wah Institution acts not only as a formal structure but as a representation of Islam Nusantara, reinforcing Islamic and national identity within a unified da’wah narrative. Strategically, NU’s da’wah is designed to adapt to shifting social, cultural, and technological landscapes by emphasizing participatory methods, utilizing digital media, and incorporating local cultural elements. These three dimensions work together to form a da’wah model that is responsive to contemporary challenges while deeply rooted in the Ahlussunnah wal Jama’ah tradition.